PEMILIHAN TEMPAT WISATA PALING DIREKOMENDASIKAN DI KOTA METRO DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) STUDI KASUS MAHASISWA KOTA METRO - Pratama, Ahmad Wahyu; Saprudin, Usep (Institut Bakti Nusantara, 2024)
Traveling is a necessity for everyone, traveling is the best way to relieve stress that is being experienced, whether in the form of stress from work pressure, stress due to many college assignments, and other stress. Traveling is more memorable when done with loved ones such as with family, with partners, and also with closest friends. However, determining a tourist spot according to everyone's wishes is not easy, especially since the choice of tourist spots is not small. Metro City is one of the cities in Lampung province that has a relatively large number of stunning tourist attractions. From the problem above, a decision support system can be developed to choose the right recreation area using the Simple Additive Weighting method. The criteria needed to make the following agreement are budget, interval, age, facilities and time. As a result of this study, the best alternative recommendations for tourist areas in Metro City were made.